A theory of trade in a global production network - E. M. Bosker; Bastian Westbrock (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2014)
This paper develops a novel theory of trade in a global supply chain. We expand on a monopolistic competition trade model. Countries produce both intermediate and final goods that are sold domestically or, incurring country-pair specific trade costs, internationally. This links countries in a multi-stage production network. In the unique general equilibrium of the model, goods prices and wages in each country depend on the entire structure of trade connections. Drawing on methods from the social network literature, we then determine each country's importance in the global production network and analyze the welfare consequences of a further integration of the network. Our findings highlight the role of a few key countries that bring other nations closer together by intermediating their value added. Proximity to these key countries is crucial for other nations' income growth. An accompanying empirical analysis shows strong support in favor of the predicted network effects.
Keywords: 330; global supply chains; international trade; network effects